Safety concerns on the abuse potential of esketamine: Multidimensional analysis of a new anti‐depressive drug on the market. (23rd December 2021) - Baudot, Jules; Soeiro, Thomas; Tambon, Marine; Navarro, Nicolas; Veyrac, Gwenaëlle; Mezaache, Salim; Micallef, Joëlle
Abstract: Prominent features of esketamine (e.g., similar mechanism of action as ketamine and target population) require to be vigilant regarding its benefits/risks balance and its risks of abuse in real‐life settings. The aim of this study was to review all available pharmacological and clinical data to assess the abuse potential of esketamine shortly after its marketing. This multidimensional study is a quantitative and qualitative analysis of complementary data sources, ranging from preauthorization data (i.e., fundamental pharmacology and clinical trials) to real‐life settings data (i.e., pharmacovigilance databases and web forums). According to esketamine pharmacology, its psychoactive effects play a role both in its therapeutic effect and its abuse potential. Only one out of the three short‐term efficacy trials found a significant difference between esketamine and placebo in treatment‐resistant depression. Beside adverse events that may be sought for abuse purpose (e.g., dissociation, sedation, euphoric mood, hallucination, feeling drunk, and derealization), clinical signs related to substance use disorder (e.g., tolerance, withdrawal syndrome, and drug dependence) and misuse (e.g., off‐label use) were also identified in pharmacovigilance databases. Analysis of pharmacovigilance narratives and web forums showed that esketamine psychoactive effects are appreciated by some patients, while they are badly experienced by others. Strict compliance with the market authorization, close monitoring of patients by psychiatrists, and surveillance of any signs of misuse, abuse, or dependence must be part of any treatment course.